An analytical model for rapid prediction and compensation of springback for chain-die forming of an AHSS U-channel. (August 2019) - Li, Yaguang; Liang, Zhenye; Zhang, Zhiheng; Zou, Tianxia; Li, Dayong; Ding, Shichao; Xiao, Hua; Shi, Lei
Highlights: A modified Chaboche hardening model which assumes a Hollomon–Voce combined equation and incorporates variation of elastic modulus is established. An analytical method for rapid prediction of springback of a U-channel is developed and then combined with an optimization algorithm to compensate springback. The springback compensation is validated by a chain-die forming experiment of a QP1180 U-channel by using the optimal die design. Abstract: Chain-die forming is an emerging technique for manufacturing AHSS component as an alternative to roll forming. The pronounced springback of AHSS due to their high strength is a key factor in chain-die blocks design. In this paper, a modified Chaboche hardening model that assumes a Hollomon–Voce combined equation and incorporates variation of elastic modulus is established to better describe hardening behaviors of AHSS. An analytical method for rapid prediction of springback of a U-channel is developed and then combined with an optimization algorithm to minimize springback. The springback compensation is validated by a chain-die forming experiment of a QP1180 U-channel by using the optimal die blocks. The proposed analytical modeling method provides a fast and effective tool for die block design of U-channel chain-die forming. Graphical abstract: Image, graphical abstract